2010
DOI: 10.1136/bjsm.2010.076695
|View full text |Cite
|
Sign up to set email alerts
|

Get a kick out of this: the spectrum of knee extensor mechanism injuries

Abstract: At the end of this article, the reader should be able to (1) recognise normal anatomy and anatomical variants of the extensor mechanism of the knee on various imaging modalities, including plain film, ultrasound and MRI; (2) diagnose a broad spectrum of EM injuries in adult and paediatric patients including patellar and quadriceps tendinopathy, Osgood-Schlatter disease, Sindig-Larsen-Johansson syndrome, chondromalacia patellae and patellar fractures on various imaging modalities; and (3) appreciate the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Clinically, plica may be painful with activities requiring only shallow knee flexion (eg, walking), whereas pain from quadriceps tendinopathy is provoked with activities requiring deep knee flexion. On MRI, whereas quadriceps tendinopathy may appear as diffuse thickening and increased signal of the distal quadriceps tendon at its insertion, 86 a clearly delineated lesion deep to the quadriceps tendon raises a high index of suspicion for the superior plica involvement. 43,79 The clinical presentation of localized osteochondral lesions of the inferior region of the patella or of the trochlea may sometimes closely mimic patellar tendinopathy.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Clinically, plica may be painful with activities requiring only shallow knee flexion (eg, walking), whereas pain from quadriceps tendinopathy is provoked with activities requiring deep knee flexion. On MRI, whereas quadriceps tendinopathy may appear as diffuse thickening and increased signal of the distal quadriceps tendon at its insertion, 86 a clearly delineated lesion deep to the quadriceps tendon raises a high index of suspicion for the superior plica involvement. 43,79 The clinical presentation of localized osteochondral lesions of the inferior region of the patella or of the trochlea may sometimes closely mimic patellar tendinopathy.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Houghton 21 19,25 This is supported by recent imaging studies 25 and a single-case report 23 which suggested that quadriceps tendinopathy is a distinct pathology, separate from jumper's knee and/or patellar tendinopathy. Magnetic resonance imaging (MRI) studies have differentiated the presentation of patellar and quadriceps tendinopathies, 19 and patients with quadriceps tendinopathy commonly present with pain at the insertion of the quadriceps tendon, therefore justifying why they should be considered two separate pathologies.…”
Section: Nomenclaturementioning
confidence: 80%
“…Magnetic resonance imaging (MRI) studies have differentiated the presentation of patellar and quadriceps tendinopathies, 19 and patients with quadriceps tendinopathy commonly present with pain at the insertion of the quadriceps tendon, therefore justifying why they should be considered two separate pathologies. 25 Prevalence Previous literature has acknowledged that there is a dearth of evidence pertaining to the epidemiology of most tendinopathies including quadriceps tendinopathy. 1 However, some limited literature does exist.…”
Section: Nomenclaturementioning
confidence: 99%
See 2 more Smart Citations